Writing Achievement of The Students Taught Through Peer Responses - Anggun Saptarani; Magdad Hatim; Santi Mayasari (ELT Worldwide: Journal of English Language Teaching, 2022)
This study aims to find out whether or not the writing scores of the eleventh-grade students who were taught by using peer responses were higher than those who were not taught. This methodology of research was a true experimental design and applied pre-test and post-test. The population of this study was the eleventh grade the sample was two classes were experimental and control group. By using the cluster random sampling technique two groups were taken as samples. The data collection technique used was a written test. The instrument was tested on students at Senior High School 4 of Palembang. Based on the test of students learning outcomes using the peer responses technique, they were in the good category with significant results, namely t table 5.089, significant level 0.05 with df = 48. Based on the results of this study, it could be concluded that there was a significant difference in students writing scores using peer responses, so the peer responses technique is declared effective to be used.